Evaluation of FT-Raman and FTIR-ATR spectroscopy for the quality evaluation of Lavandula spp. Honey - Anjos, Ofélia (2018)
Monofloral Lavandula spp. honey is very appreciated by consumers due to its characteristic and pleasant aroma and flavor. Given the economic importance of this type of honey, it is important to develop a rapid and non-expensive methodology that allows certifying its quality. In this context, this study aimed to compare the applicability and accuracy of FTIR-ATR and FT-Raman techniques for the quality evaluation of Lavandula spp. honey. Calibration models, with PLS regression models, were obtained for both methodologies concerning the following parameters: total acidity, reducing sugars, hidroximetilfurfural (HMF), electrical conductivity, ash, proline content, diastase activity, apparent sucrose, total flavonoids, and total phenolic contents. The calibration models had high regression coefficients, r2 (FTIR-ATR: 0.965–0.996; FT-Raman: 0.983–0.999), high ratios of performance to deviation, RPD (FTIR-ATR: 5.4–15.7; FT-Raman: 7.6–53.7), and low root mean square errors (RMSEs; FTIR-ATR: 0.005–3.0; FT-Raman: 0.004–1.02). These results corroborate the potentiality of FTIR-ATR and FT-Raman for quality evaluation and evaluation of the chemical properties of Lavandula spp. honey even though FT-Raman technique provided more accurate models.